ANALISIS PENYELESAIAN SENGKETA BANDING ATAS KASUS PAJAK PERTAMBAHAN NILAI DI PENGADILAN PAJAK (STUDI KASUS PT OP) - Sahid, Iqbal (Jurnal Mahasiswa Perpajakan, 2015)
This study is discussing implementation of tax appeal settlement on Value Added Tax (VAT) Case of PT OP in Tax Court. Tax Appeal occurs because tax audit held by Directorate General of Taxes (DGT) based on tax restitution application filed by PT OP. The purpose of this study is to determine tax appeal settlement on VAT Case of PT OP in Tax Court and the impact of Tax Court’s decision of VAT dispute. The type of this study is descriptive using qualitative approach. Study’s result shows that tax appeal settlement of PT OP is harmonius with applicable current provision. Tax Court’s decision which is fully granting of PT OP’s petition impact to tax payment’s who overpayment plus interest that is awarded to PT OP as reward. The result of this study suggests DGT to not made any adjustment based only on assumptions. Adjustment must be made based on proof which is sufficient and reliable. The study also suggests PT OP to apply VAT’s restitution every Tax Period, to avoid any fine if there is any adjusment in tax audit. Keywords: Tax Appeal, Value Added Tax, Tax Court, Appellant, Settlement